A comparative study of alternative therapies and mandibular advancement device in the management of obstructive sleep apnea - Deeptanshu Daga; Mohit Pal Singh; Prashant Nahar; Hemant Mathur; Anshit Babel; Apoorva B Daga (Wolters Kluwer Medknow Publications, 2021)
Introduction: Patients suffering from obstructive sleep apnea (OSA) face the challenge of getting the correct diagnosis and treatment. Snoring is the most common giveaway. Aim: The aim of the study was to evaluate the quality of sleep before and after the use of the appliance and while practicing yoga based on the STOP-BANG questionnaire for sleep quality, Pittsburgh Sleep Quality Index (PSQI), and Epworth Sleepiness Scale (ESS). Methodology: A total of 100 patients visiting the outpatient department (OPD) were divided into two groups of 50 each. The first group who fulfilled the criteria for the device was given a mandibular advancement device (MAD) and the second group was assigned yoga and pranayamas. Results: The first group showed a significant increase in the airway space on lateral cephalogram also with more immediate overall scores in all three questionnaires compared to the second group. Conclusion: MAD offers an inexpensive, comfortable treatment option for patients requiring immediate relief but has poor appliance compliance. However, yoga and pranayama yielded very good results although took a long time. On follow-up, the recurrence of OSA was negligible. MAD would provide immediate relief in OSA but for sustained overall benefit yoga and pranayama should be practiced.